Estimates of (co)variance components and genetic parameters for growth efficiency traits by animal model in Chokla sheep - Choudhary, Garima; Pannu, Urmila; Narula, Harvindra Kumar; Chopra, Ashish; Poonia, Narender Kumar; Nehara, Manju (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study obtained genetic data from pedigree records of Chokla lambs over 47 years (1974-2020) and 6785 records of performance were available at Central Sheep and Wool Research Institute, Bikaner, Rajasthan, India. (Co)variance components and genetic parameters of Average daily gain and Kleiber ratio were estimated by average algorithm restricted maximum likelihood (AIREML), fitting six different animal models with various combinations of direct and maternal effects. Direct heritability estimates were inflated substantially for all traits when maternal effects were ignored. The direct additive heritability h2 values for all ADGs and KRs were moderate (0.3-0.4). The maternal influence diminished as age increases and found to be important and sizeable at pre weaning stage. Negative and high estimate of covariance between direct and maternal effects, resulted highly inflated values of additive heritability. In this condition, it is more useful to use the total heritability (h2t) for evaluation of the response for selection based on phenotypic values to prevent the use of biased estimates of additive heritability. Positive correlations between ADG and KR suggested the scope of indirect selection for growth rate if lambs are selected for higher feed efficiency based on KR.
Keywords: Chokla; Correlation; (Co)-Variance components; Genetic parameters; Maternal effect